UJI ADAPTASI LIMA VARIETAS TANAMAN PADI DI LAHAN CETAK SAWAH - yoseph Wonmut; Irba Djaja; Rangga Kusumah (Musamus University, 2022)
ABSTRACT This study aims to determine the right type of rice variety according to the conditions of the paddy field in Bokem village, Merauke district and to increase the productivity of rice cultivation in Bokem village, Merauke District. This research was conducted in two locations, namely in the village of Bokem, Merauke district and the agrotechnology laboratory, Faculty of the Agriculture University of Musamus Merauke. This study used a non-factorial randomized block design (RAK). The varieties used in this study were Ciherang, Unsoed, Mamberamo, Inpago, and Pandan Fragrant varieties. Keywords: Diversity of Rice Varieties, Unsoed, Mamberamo, Chiherang, Inpago, and Pandan wangi